Corpos Antropofágicos: Supermáquina e interseccionalidades em cartoescrita de fluxos indisciplinares. - Silva, Mariah Rafaela Cordeiro Gonzaga da (2018)
This study aims to reflect the dynamics of forces that cross the experience all those thought during a certain time as subalterns (SPIVAK, 2010). As demonstrated on the following pages, the "subalterns" have always done more than to speak, so we understood that it was necessary an investiment to invert the notion of subalternity by devouring it. In effect, the "subalterns" were protagonists at all moments of our recent history, however their legitimacy got into a violent process that aims to subjugate their vital potency. Through the colonialism, violence - and its economic peculiarities - was spread by the world and their destructive force were leading our subjectivities; the colonial unconscious indicates that the nefarious forces still survive in us, in different ways; from rape, to racism and transphobia to starvation etc. This way, we found out there is a strong process of despontency of our subjetivitivities which forms of resistance are analyzed on this essay though the notion of anthropophagy. The colonial effect is to create death, but death isn’t dissociated at any moment of life, therefore the group of things which creates ways of existentialism goes though huge machines that connected one to another “makes” a supermachine which we named biome; life does not stop producing life, even when it produced deaths. The subjectivation processes are linked, change according to each regime of reference, but the final components do not “change”: the bodies. We believe that the body enters into gears of subjectivation and production of meaning, but the body is the body even when it is fractured. This study, however, proved to be inconclusive, not because of a lack of resources or epistemological material, but fundamentally because life never concludes, it always opens up.